Perkembangan Ekonomi Dan Administrasi Pemerintahan Masa Dinasti Umayyah - Emi Hariyanti; Kholid Mawardi (Departement of Mathematics Education, 2023)
The type of research used is literature research or literature study where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. Literature research or literature research is research whose place of study is literature or literature. All Muslim regions speak one language, Arabic, as their official language. However, all cultural expressions were also expressed in Arabic then also non-Arabs began to participate in the building of